2013
DOI: 10.1080/14786435.2013.790566
|View full text |Cite
|
Sign up to set email alerts
|

The most stable crystal structure and the formation processes of an order-disorder (OD) intermetallic phase in the Mg–Al–Gd ternary system

Abstract: The most stable crystal structure for an 18R-type order-disorder (OD) intermetallic phase in the Mg-Al-Gd ternary system and its formation processes by annealing at 525 °C have been investigated by means of transmission electron microscopy (TEM) and scanning transmission electron microscopy (STEM). The most energetically favourable polytype at 525 °C is found to be the structurally simplest one, a maximum degree of order (MDO) polytype (monoclinic, 1M, space group: C2/m) that is described with a single stackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 27 publications
6
33
0
Order By: Relevance
“…For the OD groupoid family of the C 3 -type, six MDO polytypes are derived [15,18]. Similarly to the case of the 18R-type Mg-Al-Gd LPSO/OD phase [13,18], the crystal structure of the 18R-type Mg-Zn-Y LPSO/OD phase exhibits a tendency to transform from the one with the one-dimensional stacking disorder into a fully-ordered one after prolonged heat-treatment [17]. The stacking sequences of the structural blocks observed in the 18R-type Mg-Zn-Y LPSO/OD phase heat-treated at 500°C for 300 h (Fig.…”
Section: R-type Mg-zn-y Lpso/od Phasementioning
confidence: 98%
See 2 more Smart Citations
“…For the OD groupoid family of the C 3 -type, six MDO polytypes are derived [15,18]. Similarly to the case of the 18R-type Mg-Al-Gd LPSO/OD phase [13,18], the crystal structure of the 18R-type Mg-Zn-Y LPSO/OD phase exhibits a tendency to transform from the one with the one-dimensional stacking disorder into a fully-ordered one after prolonged heat-treatment [17]. The stacking sequences of the structural blocks observed in the 18R-type Mg-Zn-Y LPSO/OD phase heat-treated at 500°C for 300 h (Fig.…”
Section: R-type Mg-zn-y Lpso/od Phasementioning
confidence: 98%
“…Published by Elsevier Ltd. All rights reserved. annular dark-field (HAADF) STEM and have revealed the following features [13,15,17,18]. First, each structural block in the Mg-Al-Gd LPSO phases have a long-range in-plane order, which is characterized by a periodic arrangement of Al 6 Gd 8 atomic clusters with the L1 2 -type atomic arrangement in the Gd and Al-enriched four consecutive atomic planes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent results on the crystal structure analysis for the 18 R -type LPSO phase in the Mg-Al-Gd system, however, revealed that the LPSO phase in the Mg-Al-Gd system should not be described as a ‘LPSO’ phase any longer in a strict sense in crystallography because of the existence of the in-plane ordering of Gd and Al atoms in the four consecutive atomic layers enriched with them in the 6-layer structural block 15 . Instead, the crystal structure of the ‘LPSO-type’ phases in the Mg-Al-Gd system is best described with the concept of the order-disorder (OD) structure 1523 , in which a crystal structure is described with the symmetry of an OD layer (corresponding to a 6-layer structural block) and the relative relation between adjacent two OD layers 15,17,18 . Then, there is a possibility that a series of LPSO-type phases with an OD structure (i.e., OD phases) is formed in Mg-Al-RE ternary systems, although the OD phases have recently been found to develop also in the Mg-Zn-Y system when the Zn/Y concentrations are high 2426 .…”
Section: Introductionmentioning
confidence: 99%
“…S1(a) of Supplementary) 15 . In addition, the formation of L1 2 -type atomic clusters is common to both the OD and LPSO phases in the Mg-Al-Gd and Mg-Zn-RE ternary systems 15,16,25,26 and has been considered to play a key role in the formation of the OD and LPSO phases 17,2730 . Furthermore, recent first-principles calculations have predicted that the OD phases in the Mg-Al-RE and Mg-TM-RE ternary systems are stabilized by the inclusion of an additional Mg atom in the centre of each L1 2 -type atomic cluster 3136 .…”
Section: Introductionmentioning
confidence: 99%